Rewiring global networks at local events: congresses in the stock photo trade - Panitz, Robert; Glückler, Johannes (Global networks, 2017)
Digital technologies have enabled the geographical expansion of production and the distribution of creative goods and communication. Simultaneously, the number of trade fairs and congresses has increased. This rise of temporary encounters has led to theorizations of events as marketplaces, learning sites and field-configuring practices. This article elaborates on the metaphor of rewiring to propose and empirically demonstrate a further role of industry events for global business. Drawing on the case of the global stock photo trade, we use a unique survey to map the global network of sales partnerships as well as interviews conducted at international lead congresses to demonstrate how these events are enacted as social relays. Our findings demonstrate how temporary face-to-face contact facilitates long distance relationships between organizations and how it dynamically shapes the global industry network. Thus, we contribute to closing the gap between social action at the micro level, organizational linkages at the meso level and the structure of global industry networks at the macro level.